Creating National Resilience through State Defence and Student Character at Gerakan Sekolah Belajar - Wiwik Handayani; Hariyo Sulistyantoro; Rizky Dermawan; Erna Tri Rusmala Ratnawati (Jurnal Pendidikan Indonesia, 2023)
The crisis of national resilience in the younger generation has been widely discussed, marked by the formation of KOMCAD (Reserve Commander) for students. This action was formed to increase the value of state defence as the nation's next generation. Forming individual character takes a long time, so primary and secondary schools should immediately create a curriculum that includes state defence subjects. The problem is that there are still limited schools implementing the state defence subject curriculum, so this study aims to analyze the effect of state defence on national security and student character, as well as the effect of student character on national security in "Gerakan Sekolah Belajar". This study uses a quantitative approach to the type of causality research. This study's population was school students in the "Gerakan Sekolah Belajar", which 194 junior high school students then took as a sample. It can be concluded from the study's results that state defence has a positive and significant effect on national security and student character, and student character has a positive and significant effect on national security in "Gerakan Sekolah Belajar". The implications of this research provide an initial basis for making policies regarding the learning curriculum to build the character of students who love the country by building national resilience.